Predicting problems of Tagalog high school students in learning English inflections through contrastive analysis - Escueta, Julita Lim 1938- (publisher not identified], 1965)
The problem of this study is on the differences between English and Tagalog systems of noun, pronoun, and verb inflections. It shows a descriptive-contrastive analysis of the two inflectional systems, class by class, and category by category. As a result of the contrastive analysis, the writer has predicted specific problems in recognition and production among Tagalog high-school students learning inflections of nouns, pronouns, and verbs in English.